Integrated Geotechnical Analysis of Allophanic Volcanic Ash Soils: SDMT and Laboratory Perspectives - Eddy Fernando Sanchez; Jorge Albuja-Sánchez; Maritza Córdova (Applied Sciences)
The geological study area is volcano-tectonic in nature. Microscopic observations and mineralogical analyses revealed the presence of allophane and diatom clusters whose mineral compositions coincided with weathered andesites and dacites. Edometric consolidation tests showed a high porosity and a reduction in the void ratio by up to five times. These are highly compressible soils with a Cc/Cs ratio of 12 to 15 and a specific gravity (Gs) of 2.4. Low initial bulk density (1.10 Mg/m3), high plasticity, and SUCS (OH) classification are typical of soft soils, with an effective friction angle (ɸ’CD) of 25.5° to 30° and effective cohesion (c’CD) of 11.90 to 47.27 KPa. The shear wave velocity for the first 10 m (Vs10) on average ranged from 78 m/s to 120 m/s, whereas that for the first 30 m (Vs30) was 169 m/s. The permeability, which was calculated indirectly, was between 2 × 10−7 and 3 × 10−8 m/s. With an organic matter content between 5% and 25%, the Caupicho soil is an organic mineral sediment that is not considered peat (non-peat). The results of this study serve as a basis for future analyses of soil dynamics, bearing capacity, and consolidation settlements in the medium and long term in an area of high urban growth in southern Quito, Ecuador.